Liability of a court enforcement officer and the State Treasury for damage caused in the performance of a court enforcement officer duties - Kuniewicz, Zbigniew; Tomczyk, Adriana (Ius Novum, 2024)
The purpose of this article is to clarify doubts surrounding the liability of the court enforcement officer and the State Treasury for damages under Article 36 of the Act on Court Enforcement Officers. It considers the constitutional model of liability for damages caused by unlawful actions of a public authority, as well as civil law regulations concerning the general rules for compensating damage. The conclusions drawn from the discussion in this article include, inter alia, the following findings: (i) Article 36 CEOA provides an independent basis for the tort liability of a court enforcement officer, premised on the unlawfulness of the court enforcement officer’s conduct, regardless of fault; (ii) damage subject to compensation under Article 36 CEOA includes any damage to the legally protected goods of the affected entity, encompassing both material and non-material damage (i.e., compensation for harm suffered); (iii) in relation to this liability, a narrow interpretation of unlawfulness should be applied, one that references the constitutional approach to the sources of law (Articles 87–94 of the Constitution).